A Synthesis of the Upper Arctic Ocean Circulation During 2000–2019: Understanding the Roles of Wind Forcing and Sea Ice Decline - Wang, Qiang; Danilov, Sergey (Frontiers in Marine Science, 2022)
Major changes have occurred in the Arctic Ocean during 2000--2019, including the unprecedented spin-up of the Beaufort Gyre and the emergence of Arctic Atlantification in the eastern Eurasian Basin. We explored the main drivers for these changes by synthesizing numerical simulations and observations in this paper. The Arctic atmospheric circulation was unusual in some years in this period, with strongly negative wind curl over the Canada Basin. However, the wind-driven spin-up of the Beaufort Gyre would have been much weaker had it not been for Arctic sea ice decline. The sea ice decline not only fed the ocean with meltwater, but also made other freshwater components more available to the Beaufort Gyre through mediating the ocean surface stress. This dynamical effect of shifting surface freshwater from the Eurasian Basin towards the Amerasian Basin also resulted in the Arctic Atlantification in the eastern Eurasian Basin, which is characterized by halocline salinification and the uplift of the boundary between the halocline and the Atlantic Water layer. Contemporarily, the sea ice decline caused a strong warming trend in the Atlantic Water layer. The Empirical Orthogonal Function (EOF) analysis of Arctic annual sea surface height for this period reveals that the first two modes of the upper ocean circulation have active centers associated with the Arctic Oscillation and Beaufort High variability, respectively. In the presence of sea ice decline the first two EOFs can better distinguish the ocean variability driven by the two atmospheric circulation modes. Therefore, the major changes in the Arctic Ocean in the past two decades are indicators of climate change as is the sea ice retreat. Our synthesis could help assess how the Arctic Ocean might change in future warming climate.